Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Ayam Melalui Proses Sol Gel Dengan Variasi Rasio Ca/P Dan Konsentrasi Asam Nitrat - Adrian, Melisa; A, Yelmida; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Hydroxyapatite Ca10(PO 4)6(OH)2 is a compound of calcium phosphate which is a bioactive ceramic material with high bioafinity and anorganic components main constituent of bones and teeth. Hydroxyapatite (HAp) can be used as a bone implant, adsorbents and catalysts. Hydroxyapatite synthesis can be performed by using raw materials which is rich in calcium such as egg shell. Calcium in the form of Calcium Carbonate (CaCO3) on the chicken egg shell in this study changed to be precipitated Calcium Carbonate (PCC) through the process of carbonation. PCC from chicken egg shells used as a source of calcium in the synthesis of HAp with a sol gel method. In the synthesis of HAp, Ca and P ratio varied from reactant (Ca/P: 1.57; 1.67; and 1.77) and the concentration of HNO 3 (0.3M; 0.4M; 0.5M) at the stage of PCC dissolution. The analysis result of HAp synthesis with Fourier Transform Infrared Spectroscopy (FTIR) showed that the apatite compound has been formed with the absorption of PO4 3- and OH - ion at the wave number 1,025 and 3,625 cm -1. The highest transmittance obtained on the sample at the concentration of 0.4M HNO3 with the ratio Ca/P 1.77; a concentration of 0.5M HNO3 with the ratio of Ca/P 1.67 and a concentration of 0.3M HNO3 with the ratio Ca/P 1.57. Based on X-ray Diffraction (XRD) analysis, the best HAp obtained in ratio of Ca/P 1.77 and concentration of HNO 3 0.4M with hexagonal crystal structure, with particle size was 46.06 nm. SEM-EDX photograph showed the morphological form of agglomerates. The mole ratio of Ca and P hydroxyapatite from PCC of egg shell was 1.55 and 8.968 m 2/g surface area.Keywords: Precipitated Calcium Carbonate (PCC), Chicken Egg Shell, Hydroxyapatite, Sol gel Method